Whole genome characterization of a G6P[5] rotavirus A strain isolated from a stray cat in Japan - Kaneko, Miho; Mochizuki, Masami; Nakagomi, Osamu; Nakagomi, Toyoko (Veterinary microbiology, 2016)
•An unusual G6P[5] rotavirus A strain, FRV537, was isolated from a stray cat.•The genotype constellation of FRV537 was G6-P[5]-I2-R2-C2-M2-A13-N2-T6-E2-H3.•FRV537 showed a close relationship with bovine rotaviruses in all genome segments.•The cat was most probably infected with a bovine rotavirus strain. The whole genome of an unusual G6P[5] rotavirus A strain named FRV537, which was isolated from a stray cat in Japan, was characterized to determine its species of origin. The genotype constellation of FRV537 was G6-P[5]-I2-R2-C2-M2-A13-N2- T6-E2-H3. No known feline rotavirus has this genotype constellation; the Japanese equine strain OH-4 is the only known strain that does. While FRV537 shares the same genotype with some feline rotaviruses in all genes except those encoding VP4 and NSP1, none of these genes are closely related to those of known feline rotaviruses. By contrast, G6P[5] is almost exclusively present in bovine rotaviruses. The VP7 and VP4 genes of FRV537 formed a lineage with typical bovine rotaviruses with high bootstrap values. As to the internal capsid and nonstructural gene constellation, three bovine rotavirus strains had a constellation identical to that of FRV537. Moreover, each of the genotypes of FRV537 was found to be a common bovine genotype. In addition to the high nucleotide sequence identities between FRV537 and bovine rotaviruses in each genome segment (≥95%), phylogenetic analysis revealed a close relationship to bovine/artiodactyl rotaviruses. Thus, the molecular and phylogenetic evidence suggests that FRV537 isolated from a stray cat was of bovine rotavirus origin.